1993
DOI: 10.1083/jcb.120.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Correctly sorted molecules of a GPI-anchored protein are clustered and immobile when they arrive at the apical surface of MDCK cells.

Abstract: Abstract. Glycosyl-phosphatidylinositol (GPI)-anchored proteins are sorted to the apical surface of many epithelial cell types. To better understand the mechanism for apical segregation of these proteins, we analyzed the lateral mobility and molecular associations of a model GPI-anchored protein, herpes simplex virus gD1 fused to human decay accelerating factor (gD1-DAF) (Lisanti, M. P., I. W. Caras, M. A. Davitz, and E. . J. Cell Biol. 109:2145-2156 shortly after arrival and after longterm residence at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 52 publications
2
61
0
1
Order By: Relevance
“…It was speculated that the size, glycosylation, and interactions of the ecto-domain of the GPIanchored proteins with the extracellular matrix, other TM receptors, or cortical cytoskeletal corrals could be a potential explanation ( 37,39 ). FRAP-based studies also showed that apically sorted GPIs are immobile just after reaching the cell surface, and their mobility increases as they become long-term residents at the cell surface, suggesting that GPI-anchored proteins are delivered to the membrane in a clustered form ( 40 ). Studying the dynamics of GPI-anchored proteins ( 41 ) provided a scale dependence to GPI-anchored protein diffusion, which suggested that they diffuse freely as individual molecules over a larger length scale, but may dynamically partition into raft domains.…”
Section: Diffusional Dynamics Of Gpi-anchored Proteinsmentioning
confidence: 91%
“…It was speculated that the size, glycosylation, and interactions of the ecto-domain of the GPIanchored proteins with the extracellular matrix, other TM receptors, or cortical cytoskeletal corrals could be a potential explanation ( 37,39 ). FRAP-based studies also showed that apically sorted GPIs are immobile just after reaching the cell surface, and their mobility increases as they become long-term residents at the cell surface, suggesting that GPI-anchored proteins are delivered to the membrane in a clustered form ( 40 ). Studying the dynamics of GPI-anchored proteins ( 41 ) provided a scale dependence to GPI-anchored protein diffusion, which suggested that they diffuse freely as individual molecules over a larger length scale, but may dynamically partition into raft domains.…”
Section: Diffusional Dynamics Of Gpi-anchored Proteinsmentioning
confidence: 91%
“…Today, the concept of lipid rafts has evolved and association with lipid rafts is considered not sufficient for apical targeting. Fifteen years old observations (Hannan et al, 1993) and recent work (Paladino et al, 2004) suggest that the ability of glycosylphosphatidyl inositol anchors to act as apical sorting signals depends on clustering through their carbohydrate or proteinaceous moieties (RodriguezBoulan et al, 2005). It has been proposed that glycosylphosphatidyl inositol-protein clustering may be mediated by lectins of the galectin class (reviewed by Fullekrug and Simons, 2004).…”
Section: Polarized Trafficking Machinerymentioning
confidence: 99%
“…Early experiments with a clonal MDCK cell line resistant to killing by the lectin concanavalin A (ConA) (Meiss et al, 1982) suggested an explanation. ConA-resistant MDCK cells were unable to correctly sort GPI-APs to the apical surface, and fluorescence recovery after photobleaching (FRAP) experiments showed that, unlike wild-type MDCK cells, they were unable to 'cluster' GPI-APs into immobile aggregates, suggesting that "correctly sorted GPI-APs are clustered before arrival at the apical surface" (Hannan et al, 1993). More recent experiments by Zurzolo and co-workers (Paladino et al, 2004) provided additional evidence for a key clustering event in apical targeting of GPI-APs.…”
Section: Lipid Rafts In Apical Targetingmentioning
confidence: 99%
“…Journal of Cell Science 122 (23) (Lisanti et al, 1989a;Brown et al, 1989;Brown and Rose, 1992;de Marco et al, 2006;Delacour et al, 2005;Hannan et al, 1993;Paladino et al, 2008;Paladino et al, 2004;Vieira et al, 2005) (Gundersen et al, 1991;Deora et al, 2005;Diaz et al, 2009) (Hoekstra et al, 2004;Slimane et al, 2003;Wakabayashi et al, 2006) ATP7B (Menkes) copper transporter ? ?…”
Section: Apical Trafficking Machinery and Routesmentioning
confidence: 99%